Effects of a functional rehabilitation program designed by the arronches care unit for a patient with stroke: a case report - Simeão, Ana (2018)
This study describes the effect of a Functional Rehabilitation Program (FR) designed for the recovery of stroke patients. A new FR approach for stroke patients was experienced obeying the internment protocol used in the Continuing Care Units Mean Duration and Rehabilitation. According to the law (DC 101/2006), the protocol includes the patient initial assessment and the design of an individual FR program of treatment developed until 90 days; moreover, suggests evaluations after 30 days of hospitalization and before day 90 (Girão & Guerreiro, 2011). Case Description: Patient aged 74 yrs, diagnosed with left capsular hematoma striatum due to ischemic stroke. Background: hypertension and alcoholism. In the initial evaluation, the patient was oriented in time and space, he showed left hemiparesis, hearing and visual acuity impairment, motor programming deficit, balance at setting position compromised, inability to walk, and high dependence in basic and instrumentals activities of daily living (BADLs and IADLs). Evolution prognosis: reserved. Intervention: The FR program (5 days/week) incorporated three areas: Rehabilitation Nursing (RN), Physiotherapy (P), and Psychomotor Rehabilitation (PR).The RN performed BADLs relearning with a nurse; the P used the Bobath method; and the PR, as innovation, combined the traditional Brunnstrom method with sensorimotor stimulation targeting ontogenetic reliving. Evaluations were performed in the pre-intervention (PI), after 30 intervention days, and at the end of the program - before day 90. BADLs were accessed using the Barthel Index, and the IADLs using the Lawton Index. Global mobility was measured using Mobility Scale for the Elderly (EMI) and the six minutes walking test. The patient improved BADLs (Barthel, score: PI = 14; 30 days = 37; 90 days = 62) and IADLs (Lawton score: PI = 0; 30 days = 5; 90 day = 7), as well as mobility (EMI score: PI = 0; 30 days = 6; 90 day = 11), having reacquired the walking ability (walking test: PI = 0 m; 30 days = 38 m; 90 day = 50 m). The performed interdisciplinary intervention showed positive effects on the recovery of the stroke patient; specifically induced increases in his mobility and ability to perform BADLs and IADLs. These results suggest that interdisciplinary RF programs including ontogenetic reliving would be effective for the recovery of stroke patients with poor prognosis of evolution.